Performance Analysis of Dual-Hop THz Transmission Systems over α-μ Fading Channels with Pointing Errors - Li, Sai; Yang, Liang (IEEE internet of things journal, 2022)
In this paper, the performance of a dual-hop relaying terahertz (THz) wireless communication system is investigated. In particular, the behaviors of the two THz hops are determined by three factors, such as the deterministic path loss, the fading effects, and pointing errors. Assuming that both THz links are subject to the α-μ fading with pointing errors, we derive exact expressions for the cumulative distribution function (CDF) and probability density function (PDF) of the end-to-end signal-to-noise ratio (SNR). With these statistical expressions, some important performance metrics are evaluated, like the outage probability, average bit error rate, and average channel capacity. Moreover, the asymptotic analyses are presented to obtain more insights. Results show that the dual-hop relaying scheme has better performance than the single THz link. Furthermore, the system diversity order depends on the fading parameters and pointing errors of both THz links. In addition, we extend the analysis to a multi-relay cooperative diversity system and derive the asymptotic symbol error rate expressions. Finally, the derived analytical expressions are verified by the Monte Carlo simulation.